A role of the sires and dams in the hermaphrodite phenomenon linked with polled Damascus goat breed - M. Roukbi; Kh. Al-najar; K. Fatal (Iraqi Journal of Veterinary Sciences, 2013)
The selection for polled character as preferential in Damascus breed leads to spread homozygous individuals for the polled gene and polled intersexes and consequently further economic losses in this breed. It’s very important to study the genetic origin, the role of sirs and dams in the development of intersexuality linked with hornlessness, and evaluate some other effects in the excess of the intersexes in caprine herd. To perform this work data of 52 intersexes issues from mating 19 polled bucks with 12 horned and 37 polled goats in Humeimeh research station, belonging to General commission for agricultural scientific research, were collected and analyzed by mean of Chi-Square (SAS, 1998). The results showed the statistical effect of sires (P≤0.007) and the unstististical effect (P≥0.05) of dames on the development of polled intersexes in Damascus goat breed. The number of kids intersexes were repeated 10, 5, 4, 3, 2 and 1 for 1, 2, 2 and 1, five and eight sire number respectively. Whereas the number of kids intersexes were repeated only 2 and 1 for 3 and 46 goat number respectively. The sex of the kids, kidding type and horned goat character have all highly significant effect (P≤0.001) and this because intersex cases issues of single births and twin birth: twin to male, twin to female, and triple births: twin to male and female, and twin to tow males respectively were repeated 17, 18, 14, 2 and 1 respectively. Also, single births, twin births and triple births were repeated 17, 32 and 3 respectively. Cases of intersexuality issues from horned and polled goats were repeated 14 and 38 respectively. It was concluded the important role of hornlessness genetic and multiple births in the development of polled intersexes in Damascus goat breed.